2011
DOI: 10.2108/zsj.28.526
|View full text |Cite
|
Sign up to set email alerts
|

Origin and Possible Role of Males in Hermaphroditic AndrogeneticCorbiculaClams

Abstract: Hermaphroditic Corbicula leana clams reproduce by androgenesis and have been regarded as simultaneous hermaphrodites. To date, there has been no report on the occurrence of male clams in hermaphroditic Corbicula. In an irrigation ditch in Shiga Prefecture, we found that 78.2% of C. leana specimens were males and 21.8% were hermaphrodites. Microfluorometric analysis revealed that males were diploids and hermaphrodites were triploids. All males produced nonreductional and biflagellate spermatozoa. The sequence a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
20
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 20 publications
4
20
0
2
Order By: Relevance
“…Within the genus Corbicula, biflagellate sperm are unique to androgenetic lineages (including males coexisting with androgens), as far as is known. Moreover, the situation of androdioecy, found recently in C. leana (Houki et al, 2011), is very rare in the animal kingdom (Weeks et al, 2006).…”
Section: Androgenetic Spermmentioning
confidence: 96%
See 4 more Smart Citations
“…Within the genus Corbicula, biflagellate sperm are unique to androgenetic lineages (including males coexisting with androgens), as far as is known. Moreover, the situation of androdioecy, found recently in C. leana (Houki et al, 2011), is very rare in the animal kingdom (Weeks et al, 2006).…”
Section: Androgenetic Spermmentioning
confidence: 96%
“…Self-fertilization has also been suggested in Corbicula (Ikematsu and Yamane, 1977;: embryos were found in the visceral mass, within the gametogenic follicles, whereas most embryos are usually incubated in the gills in hermaphrodites (for example, Glaubrecht et al, 2006). Recently, Houki et al (2011) found a Japanese population of C. leana that contains both males and hermaphroditic individuals. The cytological and genetic results suggest androdioecy, with androgenetic males fertilizing eggs of hermaphrodites.…”
Section: Reproductive Characteristicsmentioning
confidence: 98%
See 3 more Smart Citations